2008
DOI: 10.1128/iai.01428-07
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1β Modulates Proinflammatory Cytokine Production in Human Epithelial Cells

Abstract: Periodontitis is a chronic human inflammatory disease initiated and sustained by dental plaque microorganisms. A major contributing pathogen is Porphyromonas gingivalis, a gram-negative bacterium recognized by Toll-like receptor 2 (TLR2) and TLR4, which are expressed by human gingival epithelial cells (HGECs). However, it is still unclear how these cells respond to P. gingivalis and initiate inflammatory and immune responses. We have reported previously that HGECs produce a wide range of proinflammatory cytoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(76 citation statements)
references
References 31 publications
3
72
0
1
Order By: Relevance
“…As with IL-6 (31), IL-1b secretion is increased in WAT during obesity (32), and both cytokines are known to act in concert in diverse biological process (33). Il-1b is also implicated in a "secondary" inflammatory response, regulating the production of cytokines and chemokines as G-CSF, IL-6, or IL-8 (34)(35)(36). Interestingly, our study showed that neutralization of IL-6 and IL-1b in cocultures led to a decreased inflammatory response and a rescue of some metabolic and secretory alterations of adipocytes (i.e., G-CSF, CXCLs, and IL-8).…”
Section: Discussionmentioning
confidence: 99%
“…As with IL-6 (31), IL-1b secretion is increased in WAT during obesity (32), and both cytokines are known to act in concert in diverse biological process (33). Il-1b is also implicated in a "secondary" inflammatory response, regulating the production of cytokines and chemokines as G-CSF, IL-6, or IL-8 (34)(35)(36). Interestingly, our study showed that neutralization of IL-6 and IL-1b in cocultures led to a decreased inflammatory response and a rescue of some metabolic and secretory alterations of adipocytes (i.e., G-CSF, CXCLs, and IL-8).…”
Section: Discussionmentioning
confidence: 99%
“…They were grown as previously described (28) to sub-confluence, sub-cultured, and challenged as described (2,29,30). At confluence, they were challenged with heat-inactivated P. gingivalis (strain 33277) or 1 g/ml FSL-1 (Pam2CGDPKHPKSF, a synthetic diacylated lipoprotein and a specific ligand for TLR-2) (InvivoGen, CA).…”
Section: Methodsmentioning
confidence: 99%
“…2A). The time points for this chronic infection were carefully chosen based on our previously published results on P. gingivalisinduced inflammatory cytokine response in gingival epithelial cells (Eskan et al 2008;Stathopoulou et al 2009;Stathopoulou et al 2010). By using this method, we successfully induced tolerance to P. gingivalis (live bacteria at MOI: 5) in normal epithelial cells.…”
Section: Chronic P Gingivalis Infection Modelmentioning
confidence: 99%